Visitabilidade-vivenciabilidade em assentamentos informais : um estudo da acessibilidade de percursos urbanos no Conjunto Santa Terezinha em Fortaleza-CE - Mamede, Lia Costa (2011)
This research approaches the issue of accessibility in informal settlements, seeking for the challenges and limits defined by informal urban settings, about the application of accessibility parameters. Take the empirical universe as the Conjunto Santa Terezinha, located in Fortaleza- Ce. Initially, the study presents a reflection about the housing issue in Brazil and the informal settlementes in view of the Right to the City. In this sense, the main references are, the works of Suzanne Pasternak (2008), Nabil Bonduki (1998) and Erminia Maricato (1996-97), among others. Follows with the discussion of the concepts and classifications of this type of settlement, making a content analysis of legislation and regulations relating to accessibility and proposed the discussion of the accessible route as the right strategy for the city. In another step, the methodology of 'walking together' created by Dischinger (2000) was applied in a passage previously chosen, which the researcher follows the disabled person during the journey through city making records like photos and video. The comments and perceptions are compared to the spatial analysis of urban morphology, made from the method of Del Rio (1990) and Panerai (2006), and the parameters of NBR 9050. Knowledge of the area is enriched by the methodology of the production of space made by Henri Lefebvre in his book 'The production of space' (1974) with these categories: space conceived, perceived and lived. Another key reference of this author it s the book 'The Right to the City' (991), which allowed in-depth reflections on the social function of town. In conclusion, the study finds that to guarantee a minimum access conditions in informal sittlements it´s necessary to know the specifics of their morphology, their relations and urban practices in view of the visitability- experiencebility, describing it as complementary concepts